Of mice and men: Laboratory murine models for recapitulating the immunosuppression of human sepsis - Wang, Ning; Lu, Yongling; Zheng, Jiang; Liu, Xin (Frontiers in Immunology, 2022)
Prolonged immunosuppression is increasingly recognized as the major cause of late phase and long-term mortality in sepsis. Numerous murine models with different paradigms, such as lipopolysaccharide injection, bacterial inoculation, and barrier disruption, have been used to explore the pathogenesis of immunosuppression in sepsis or to test the efficacy of potential therapeutic agents. Nonetheless, the reproducibility and translational value of such models are often questioned, owing to a highly heterogeneric, complex, and dynamic nature of immunopathology in human sepsis, which cannot be consistently and stably recapitulated in mice. Despite of the inherent discrepancies that exist between mice and humans, we can increase the feasibility of murine models by minimizing inconsistency and increasing their clinical relevance. In this mini review, we summarize the current knowledge of murine models that are most commonly used to investigate sepsis-induced immunopathology, highlighting their strengths and limitations in mimicking the dysregulated immune response encountered in human sepsis. We also propose potential directions for refining murine sepsis models, such as reducing experimental inconsistencies, increasing the clinical relevance, and enhancing immunological similarities between mice and humans; such modifications may optimize the value of murine models in meeting research and translational demands when applied in studies of sepsis-induced immunosuppression.